Revisions of Extensive Acetabular Defects with Impaction Grafting and a Cement Cup - van Egmond, Nienke (Springer-Verlag, 2010)
BACKGROUND: Loosening of acetabular components often leads to bony defects. Management of extensive acetabular bone loss in hip revision arthroplasty can be a tremendous challenge. QUESTIONS/PURPOSES: We asked whether a reconstruction with impacted bone grafts will provide a durable and pain-free function in extensive acetabular defects. We specifically determined the (1) survival rates with the end point of revision for any reason, aseptic revision, and radiographic loosening; (2) visual analog scale (VAS) pain score, Harris hip score (HHS), and the Oxford Hip Questionnaire score (OHQS); (3) number of repeat revisions; (4) complications; and (5) radiographic loosening, wear, and radiolucencies. PATIENTS AND METHODS: We retrospectively followed 25 patients (27 hips) with extensive acetabular defects. No patient was lost to followup. Two patients died during followup. Minimum followup was 3 years (mean, 8.8 years; range, 3–14.1 years). RESULTS: Three patients (three hips) underwent repeat revision surgery and another two patients (two hips) had radiographically loose hips. The 10-year survival rate was 88% (95% confidence interval, 74.2%–100%) with the end point acetabular revision for any reason and 95% (95% confidence interval, 86.0%–100%) with the end point acetabular revision for aseptic loosening. The mean HHSs were 55 points before surgery and 72 points postoperatively. CONCLUSIONS: Acetabular reconstruction with impaction bone grafting and a cemented cup is a reliable technique with a 10-year survival rate of 88% in patients with extensive acetabular deficiencies. LEVEL OF EVIDENCE: Level IV, case series. See the Guidelines for Authors for a complete description of levels of evidence.